Women Characters As Portrayed In Folk Narratives Of The Meiteis (Journal of Namibian Studies : History Politics Culture, 2023)
Folk narratives are a genre of folk literature that includes myths, legends, folktales, epics and fairytales. As the term recommends, it describes all the narrative forms of folk or orally transmitted stories typically of a particular culture. Folk narratives reflect the culture; in a culture, they function as a guidance and transmission of knowledge, regulating and structuring societal norms and, ethics, and belief systems. Degh (1972) stated that “Folk narratives are subject to such essential changes not only when they adjust to different cultures and epochs but also when they follow internal changes within the same culture.” (1972: 59). This article will highlight the main features and characteristics of the Meiteis by analyzing the women characters and their representations in the folk narratives. This discourse will also attempt to bring out the feminist elements, if any, that exist in the folk narratives of the Meiteis, as discussions of women are vague without the features and aspects of feministic perspectives. The observations and discussion of this article will positively create an understanding of how women are represented and portrayed through the characters and plots in the folk narratives and their impact on the activities performed and the position of women in the social and cultural background of the Meiteis.